Pengaruh Celebrity Worship terhadap Problematic Internet Use pada anggota NCTzen Indonesia - Sarah Asmaussolihat; Eni Nuraeni Nugrahawati (Bandung Conference Series: Psychology Science, 2022)
Abstract. NCTzen early adults are found to still love many K-Pop celebrities and often use the internet in fangirling activities. K-Pop fans use the internet for hours and a day to access content about their idols in the form of photos, videos, articles and music through social media such as Twitter, Instagram, Lysn, Naver or other forms of platforms such as Youtube V Live. This includes excessive internet use and also leads to compulsive use of the internet. One of the big fandoms in Indonesia is NCTzens. NCTzens is a fan name of a South Korean boy group called NCT. The purpose of this study was to find out the influence of Celebrity Worship on Problematic Internet Use on NCTzen Indonesia members. The hypothesis proposed is that there is an influence of Celebrity Worship on Problematic Internet Use in early adult NCTzen Indonesia members. The hypothesis proposed is that there is an influence of Celebrity Worship on Problematic Internet Use on NCTzen Indonesia members. The study sample of 154 using purpossive sampling techniques, data collection was conducted using the Celebrity Attitude Scale (CAS, McCutcheon 2002) and Generalized Problematic Internet Use Scale 2 (GPIUS2, Caplan 2010). Data analysis uses simple regression analysis techniques. Based on the results of statistical analysis obtained the regression coefficient value of 0.000 < 0.05 with a value of b = 0.602 and a value of R2 = 0.071 which means there is a positive influence of Celebrity Worhsip on problematic Internet Use is small. Abstrak. NCTzen dewasa awal ditemukan masih menggemari selebriti K-Pop banyak dan sering menggunakan internet dalam aktifitas fangirling/fanboying-nya. Fans K-Pop menggunakan internet dalam waktu berjam-jam satu harinya untuk mengakses konten mengenai idolanya dalam bentuk foto, video, artikel dan musik melalui media sosial seperti Twitter, Instagram, Lysn, Naver atau bentuk platform lain seperti Youtube V Live. Hal tersebut termasuk kepada penggunaan internet secara berlebihan dan juga mengarah kepada penggunaan internet yang kompulsif. Salah satu fandom besar yang ada di Indonesia adalah NCTzens. NCTzens merupakan nama penggemar dari boy group asal Korea Selatan yang bernama NCT. Tujuan penelitian ini untuk mengetahui pengaruh Celebrity Worship terhadap Problematic Internet Use pada anggota NCTzen Indonesia dewasa awal. Hipotesis yang diajukan adalah terdapat pengaruh Celebrity Worship terhadap Problematic Internet Use pada anggota NCTzen Indonesia. Sampel penelitian berjumlah 154 dengan menggunakan teknik purpossive sampling, pengumpulan data dilakukan dengan menggunakan Celebrity Attitude Scale (CAS, McCutcheon 2002) dan Generalized Problematic Internet Use Scale 2 (GPIUS2, Caplan 2010). Analisis data menggunakan teknik analisis regresi sederhana. Berdasarkan hasil analisis statistik didapatkan nilai koefisien regresi 0,000 < 0,05 dengan nilai b=0,602 dan nilai R2 = 0,071 yang artinya terdapat pengaruh yang positif dari Celebrity Worhsip terhadap Problematic Internet Use yang kecil.